The efficacy of chlorhexidine dentifrice or gel on plaque, clinical parameters of gingival inflammation and tooth discoloration: a systematic review. Issue 1 (29th August 2013) - Slot, DE; Berchier, CE; Addy, M; Van der, U; Van der, GA
Abstract Aim Based on the existing scientific literature, the effect of chlorhexidine (CHX) dentifrice/gel as compared to a regular or placebo dentifrice/gel is established in healthy adults on the primary outcome parameters of plaque and gingivitis scores. As secondary parameter, tooth surface discoloration was evaluated as a side effect. Materials and methods MEDLINE, EMBASE and Cochrane Central Register of Controlled Trials were searched up to July 2013 to identify eligible studies. Included were (randomized) controlled clinical trials, regarding self‐performed brushing by adults without periodontitis with a minimum duration of 4 weeks. Results Independent screening of 389 unique titles and abstracts resulted in 16 comparisons. Of these, nine evaluated CHX dentifrice (0.4–1.0%) and 7 CHX gel (0.2–2.0%). It was not possible to perform a meta‐analysis; therefore, a descriptive analysis was carried out. Regarding plaque score reduction, the majority of the experiments using a CHX dentifrice provided a significant positive effect. All studies assessing gingival bleeding as parameter for gingivitis observed a significant reduction in favour of CHX dentifrice over placebo dentifrice. Tooth surface discoloration was more pronounced with CHX dentifrice. The combined data concerning parameters of interest for CHX gel compared with a placebo did not show a trend towards a beneficial effect on plaque and bleeding scores. Conclusions Within the limitations of this analysis, it may be concluded that toothbrushing with a CHX gel does not provide conclusive evidence. Brushing with a CHX dentifrice can be effective with regard to the control of plaque and gingivitis. Tooth surface discoloration was observed as side effect, which potentially can have a negative impact on patients' compliance.